Electronic structure and phase stability of low-temperature Ba(Fe1-xNix)2As2 superconductor - Kamaruddin K.H.; Zabidi N.A.; Rosli A.N.; Yahya M.Z.A.; Taib M.F.M. (American Institute of Physics Inc., 2024)
Indexed by Scopus/WOS